2003
DOI: 10.1186/1297-9686-35-6-457
|View full text |Cite
|
Sign up to set email alerts
|

Longitudinal random effects models for genetic analysis of binary data with application to mastitis in dairy cattle

Abstract: -A Bayesian analysis of longitudinal mastitis records obtained in the course of lactation was undertaken. Data were 3341 test-day binary records from 329 first lactation Holstein cows scored for mastitis at 14 and 30 days of lactation and every 30 days thereafter. First, the conditional probability of a sequence for a given cow was the product of the probabilities at each test-day. The probability of infection at time t for a cow was a normal integral, with its argument being a function of "fixed" and "random"… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
1

Year Published

2004
2004
2012
2012

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 16 publications
0
6
1
Order By: Relevance
“…Another explanation for the lower heritabilities in our study is probably the much lower CM frequency. In our data, the overall CM frequency was about 10% to 11% compared to 18% (Rekaya et al, 2003) and 23% (Chang, 2002;Heringstad et al, 2003;Chang et al, 2004b) in other longitudinal studies of CM.…”
Section: Random Regression Models For Clinical Mastitiscontrasting
confidence: 43%
See 3 more Smart Citations
“…Another explanation for the lower heritabilities in our study is probably the much lower CM frequency. In our data, the overall CM frequency was about 10% to 11% compared to 18% (Rekaya et al, 2003) and 23% (Chang, 2002;Heringstad et al, 2003;Chang et al, 2004b) in other longitudinal studies of CM.…”
Section: Random Regression Models For Clinical Mastitiscontrasting
confidence: 43%
“…Heritability estimates of the liability to CM from threshold models are generally higher than those from linear models (Heringstad et al, 2000). Rekaya et al (2003) reported heritabilities for test-day records of CM of 27% at day 14, 5% at day 60, 3% at day 120 and 7% at day 305, from a Bayesian threshold RRM on 329 first-lactation Holstein cows. Heringstad et al (2003) and Chang et al (2004b) studied the same data from first-lactation Norwegian cattle using similar approaches as Rekaya et al (2003).…”
Section: Random Regression Models For Clinical Mastitismentioning
confidence: 97%
See 2 more Smart Citations
“…Furthermore, two mastitis incidence scenarios were used (Table 1). Scenario one was chosen to reflect previous estimates of the incidence of mastitis in field data of Swedish first-parity cows [5,11,33], where a case of mastitis was defined as a veterinary-treated clinical mastitis. The recurrence rate of CM was based on data from the research herd of the Department of Animal Breeding and Genetics, Swedish University of Agricultural Sciences [1].…”
Section: Methodsmentioning
confidence: 99%